Risk factors associated with musculoskeletal disorders among gemstone polishers in Jaipur, India. Issue 1 (2nd January 2021) - Das, Dipayan; Kumar, Awadhesh; Sharma, Monica
Abstract : Purpose . Gemstone polishing is a highly repetitive and strenuous job which may lead to musculoskeletal disorders (MSDs) among workers. This study aimed to determine the prevalence of MSDs and their contributing factors among gemstone polishers in Jaipur, India. Materials and methods . A self-reported questionnaire study was conducted among 388 male gemstone polishers. Current working postures of the participants were evaluated using rapid upper limb assessment. Results were considered significant at p ≤ 0.05. Results . MSDs were highly prevalent among gemstone polishers, primarily in the lower back, neck, wrists/forearms and shoulders. Work-related factors including prolonged daily working hours, little recovery time, sustaining a non-neutral working posture, repetitive movements of upper limbs and individual factors including age and job tenure were significantly associated with MSDs in different body regions. Higher education led to a reduction in the occurrence of MSDs. Evaluation of working posture recommended further investigations and immediate changes in working habits of gemstone polishers to avoid serious harm and physical damage. Conclusion . Gemstone polishers in Jaipur are at high risk of developing MSDs in different body regions. Sustaining a non-neutral working posture for a long duration is a major risk factor in the current work setting.